Implementación de servidores web en plataformas linux y windows en el laboratorio de desarrollo de software de la carrera de ingeniería en informática y sistemas computacionales de la Universidad Técnica de Cotopaxi en el período académico 2013 – 2014 - De la Cruz Guanoluisa, Silvana Alexandra (2014)
The purpose of making the implementation of web servers is based on the academic needs of students; the same that allowed the development portals, web sites and web pages, in these way students will be able to practice the acquired knowledge in the classroom. The importance of the issue settled in that through the implementation of Web Server in Linux and Windows Platforms, will improve the learning processes of students as well as the creation of new applications, the same that will allow both the Technical University of Cotopaxi and the career in Software Engineering and Computer Systems will be developed in a better way. In addition you will be a didactic guide (video tutorial) specific and complete of installation and